A Temporal Network Model for Livestock Trade Systems - Ansari, Sara; Heitzig, Jobst; Brzoska, Laura; Lentz, Hartmut H. K.; Mihatsch, Jakob; Fritzemeier, Jörg; Moosavi, Mohammad R. (Frontiers in Veterinary Science, 2021)
The movements of animals between farms and other livestock holdings for trading activities form a complex livestock trade network. These movements play an important role in the spread of infectious diseases among premises. For studying the disease spreading among animal holdings, it is of great importance to understand the structure and dynamics of the trade system. In this paper, we propose a temporal network model for animal trade systems. Furthermore, a novel measure of node centrality important for disease spreading is introduced. The experimental results show that the model can reasonably well describe these spreading-related properties of the network and it can generate crucial data for research in the field of the livestock trade system. Furthermore, the model complexity indicates that it is scalable concerning the size of the network.